Economy and economics of disasters as a theoretical basis of economic security - Jaroslav SLEPECKÝ (Košická bezpečnostná revue, 2020)
Economy and economics are an indispensable basis for economic security. Ensuring an adequate level of economic growth is a basic prerequisite for the functioning and development of society. It is necessary to create conditions for economic growth that enable the required performance of the economic system. Within the framework of risk management, it is always necessary to take into account factors that may negatively affect the operation and performance of the system when creating these conditions. Disasters that can have various causes and impacts on the system under study are also such factors. Examining the causes and consequences of disasters on the economies of individual countries is very important for maintaining a functioning economy, the quality of life of the population, but also security. The article deals with the definition of basic concepts and interrelationships between economics, resp. disaster economy, economic security and security as such.